Tâches d'encre : french composition - Krueger, Cheryl L.; Fauvel, Maryse (Cengage, 2023)
"Using a process-writing approach, this third-year composition text helps students master writing skills, gain confidence as writers, discover that writing - even in a foreign language - can be a pleasure. The text is set up in a workbook format and is written entirely in French, except for the first chapter. Students broaden their repertoire of related speech acts, vocabulary, grammatical structures, and stylistic elements through three major sections. Each chapter features a model text - a literary piece, journalistic selection, or informal writing - that represents the Francophone world."--taken from publisher web site.